2010
DOI: 10.1007/s00330-010-1721-y
|View full text |Cite
|
Sign up to set email alerts
|

The cardiothoracic ratio—an inaccurate and outdated measurement: new data from CT

Abstract: The cardiothoracic ratio-an inaccurate and outdated measurement: new data from CT Abstract Cardiomegaly (and left ventricular size in particular) is well recognized to have cardiovascular prognostic significance. Cardiac assessment should be routinely performed when evaluating imaging studies encompassing the thorax, whether cross sectional or projectional. However, such measurements should be robust, readily available and practical. In this issue of European Radiology, Schlett et al. describe such a technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The standard PA CXR (taken by analog calibrated Toshiba system with this criteria: Beam limiting device, model TF-6TL-6, input 1-phase 50/60Hz AC12V, max input power 100VA, max tube voltage 150KV, filtration 1.2 mm) was taken on deep inspiration which was interpreted only by one radiologist and CTR was recorded as shown in Figure 1, which is less than 50 % in normal condition (6, 11, 17). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard PA CXR (taken by analog calibrated Toshiba system with this criteria: Beam limiting device, model TF-6TL-6, input 1-phase 50/60Hz AC12V, max input power 100VA, max tube voltage 150KV, filtration 1.2 mm) was taken on deep inspiration which was interpreted only by one radiologist and CTR was recorded as shown in Figure 1, which is less than 50 % in normal condition (6, 11, 17). …”
Section: Methodsmentioning
confidence: 99%
“…Enlarged heart size is an independent predictor of death, and an increased CTR in CXR, irrespective of its etiology, is associated with poor prognosis in middle-aged patients. This issue is indicative of great importance and necessity of early diagnosis, especially in older patients (6-11). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have not studied animals with the presence of cardiopathies, the proximity between these values suggests that, potentially, the peccary may present cut-off points close to those reported in humans for the determination of cardiac pathological alterations. Screaton (2010) demonstrated that the CTR was intimately related to the volume of the left ventricle. Rubens (1996) described CTR values of over 0.5 in humans as pathological.…”
Section: Discussionmentioning
confidence: 98%
“…Pulmonary hypertension as defined as estimated right ventricular systolic pressure > 40 mmHg by echocardiographic evaluation using simplified Bernoulli equation ( 12 13 ). The cardiothoracic ratio (CTR) was measured in the initial chest radiograph and cardiomegaly was defined as CTR > 0.55 ( 14 15 ).…”
Section: Methodsmentioning
confidence: 99%